An improved procedure to prepare 3-methyl-4-nitroalkylenethylisoxazoles and their reaction under catalytic enantioselective Michael addition with nitromethane. Issue 7 (2nd January 2015) - Moccia, Maria; Wells, Robert J.; Adamo, Mauro. F. A.
Abstract : A two-step preparation of 3-methyl-4-nitro-5-alkylethenyl isoxazoles is herein reported. These were reacted with nitromethane under phase-transfer catalysis to provide highly enantioenriched adducts (up to 93% ee). Abstract : Herein, we describe a short synthesis of 3-methyl-4-nitro-5-alkylethenyl isoxazoles and their reactivity as Michael acceptors. The title compounds reacted with nitromethane under phase-transfer catalysis to provide highly enantioenriched adducts (up to 93% ee) which were then converted to the corresponding γ-nitroacids.